Geochemical Dynamics of the Natural-Gas Hydrate System in the Sea of Marmara, Offshore Turkey - Ruffine, Livio; Fandino, Olivia; Etoubleau, Joël; Chéron, Sandrine; Donval, Jean-Pierre; Germain, Yoan; Ponzevera, Emmanuel; Guyader, Vivien; Dennielou, Bernard; Etiope, Giuseppe; Gasperini, Luca; Giovanni, Bortoluzzi; et al. (IntechOpen, 2012)
None